A review of techniques for embedding shape memory alloy (SMA) wires in smart woven composites - Mahmood Baitab, Danish; Laila Abang Haji Abdul Majid, Dayang; Junita Abdullah, Ermira; Faisal Abdul Hamid, Mohd (International Journal of Engineering and Technology, 2018)
Metallic structures, in various industrial fields such as transport and aerospace, are mostly replaced by composite structures having less weight and good strength. There is also a need of intensification of the operational dynamic environment with high durability requirements. So a smart composite structure is required that can manifest its functions according to environmental changes. One method of producing smart composite structures is to embed shape memory alloys in composite structures. Shape memory alloys (SMAs) have significant mechanical and thermodynamic properties and are available in very small diameters less than 0.2mm. These SMAs are embedded into composites for obtaining smart composites having tunable properties, active abilities, damping capacity and self-healing properties. Shape memory alloys are available in different shapes as wires, sheets, foils, strips, etc. For smart composites, mostly SMA embedded are in wire shape. Different techniques are used for embedding SMA wires in composites. SMA wires can be embedded between layers of laminates of composites, or embedded directly as reinforcement in matrix and can be woven into fabrics and used as a reinforcement. This paper reviews the different techniques of embedding SMA wires in composite structures, their pros and cons and their applications.Â Â